The Effect of Mental Training Levels of Athletes on Attitudes Towards Playing Digital Games - Tuğba Mutlu Bozkurt; Mehmet Ali Öztürk (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aimed to investigate the correlation between athletes' mental training levels and their attitudes toward playing digital games. The research group consisted of 211 active athletes from the province of Bitlis who volunteered their time. In the study, the "Personal Information Form" served as the data collection instrument, the "Mental Training Inventory in Sports" was used to assess the mental training levels of the athletes, and the "Digital Gaming Attitude Scale" was employed to determine their attitudes toward playing digital games. Following the research findings, it has been determined that there is a positive and marginally significant correlation between the athletes' mental training level and their attitudes toward playing digital games. As a result of the research, it can be concluded that the mental training levels of athletes positively influence their cognitive, affective, and psychomotor attitudes toward playing digital games.